Organization of river-sea container transportation in the Yangtze River: Processes and mechanisms. (April 2023) - Liu, Weichen; Cao, Youhui; Chen, Jianglong; Guo, Jiaying; Liang, Shuangbo
Abstract: Port systems' regionalization is driven by inland port construction and shipping logistics. Among them, riverports are unique inland ports that are connected by seaport systems and contribute to a river-sea container transportation (RSCT) organization. Through a case study of the Yangtze River, this study conceptualizes RSCT based on the "spatial-network" perspective, and the driving forces pertaining to globalization, informatization, marketization, and greenization are examined. Further, we explore the trajectory of port regionalization and supply chain terminalization between coastal and inland areas, and analyze the multiscale mechanism of transportation and service development among ports considering spatial effects. The results suggest that a significant temporal gradient exists in port regionalization between the coast and inland regions. Logistics supply chain terminalization, a component of regionalization, forms and develops only during the growing stage of regionalization. Currently, the Yangtze River port system is regionalizing and being terminalized, contributing to spatial variation between the size and capacity of different types of seaports and inland ports in providing container transportation and logistics-derived services. The framework is validated by a quantitative empirical analysis based on container barge route data and shipping service enterprise data, thus confirming the evolution process from coastal concentration to inland decentralization for both. The study findings indicate that transportation's decentralization is more significant at the macro level, and that the service cannot narrow the gap between coastal and inland areas significantly with the current development of port systems in the Yangtze River. The interaction between "spatial" and "network" has only improved in seaports, and the nexus of the transportation and logistics supply chains has not yet been formed at the macro level. This study contributes to the literature on port regionalization from the spatial network perspective and provides insight into the relationship between seaports and inland ports in a complex port system.